Blackstone's statutes on criminal law 2008 - 2009 (Oxford University Press, 2008)
Each title is ideal for use throughout the course and in exams providing the student with: ·Unparalleled coverage; Unannotated primary and secondary legislation; Detailed tables of content to aid quick and efficient research; Up-to-date and relevant material